REFORMASI PENDIDIKAN HUKUM DALAM PERSPEKTIF ABU AL-A’LA AL-MAUDUDI - H. Ibrahim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Looking at the various phenomena and human social status is not clear, especially in the state of Pakistan, the amount of depravity and nuances unsightly, and the vagueness of the law in the life of the application, push Abul A'la al-Maududi moved to reform legal education in Pakistan. Education reform law made Maududi can be seen in several steps: (1) master the Arabic language as a pre-condition for entering the legal academy; (2) study the Qur'an and hadith before beginning their education in the field of law; (3) The curriculum emphasizes the legal academy to three main subjects: the fundamentals of Islamic jurisprudence, the history of Islamic jurisprudence, and fiqh (neutral assessment on all the major schools of fiqh); and (4) together with the legal education curriculum reform, followed by upgrading the moral and character development of students.